2020
DOI: 10.1038/s41598-020-73560-9
|View full text |Cite
|
Sign up to set email alerts
|

A broad diversity in oxygen affinity to haemoglobin

Abstract: Oxygen affinity to haemoglobin is indicated by the p50 value (pO2 at 50% O2Hb) and critically determines cellular oxygen availability. Although high Hb-O2 affinity can cause tissue hypoxia under conditions of well O2 saturated blood, individual differences in p50 are commonly not considered in clinical routine. Here, we investigated the diversity in Hb-O2 affinity in the context of physiological relevance. Oxyhaemoglobin dissociation curves (ODCs) of 60 volunteers (18–40 years, both sexes, either endurance tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…As expected, hemoglobin concentration was also strongly correlated with the donors’ sex, women having an approximatively 9% lower Hb level. Higher sO 2 level in men can be explained by a stronger Hb-O 2 affinity compared to women ( Humpeler and Amor, 1973 ; Greer et al, 2018 ; Balcerek et al, 2020 ). Release of O 2 is favored by several factors such as acidosis, increased CO 2 levels and temperature, as well as elevated 2,3-Diphosphoglycerate (2,3-DPG) concentration.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, hemoglobin concentration was also strongly correlated with the donors’ sex, women having an approximatively 9% lower Hb level. Higher sO 2 level in men can be explained by a stronger Hb-O 2 affinity compared to women ( Humpeler and Amor, 1973 ; Greer et al, 2018 ; Balcerek et al, 2020 ). Release of O 2 is favored by several factors such as acidosis, increased CO 2 levels and temperature, as well as elevated 2,3-Diphosphoglycerate (2,3-DPG) concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cardiopulmonary function, it was found that the exercise-induced arterial hypoxemia at high altitude was more closely related to the heart rate in men than that in women, while ventilation and energy expenditure contributed more in women ( Horiuchi et al, 2019 ). In the aspect of oxygen transport and utilization, it was reported that although the hemoglobin content of women was lower than that of men, the affinity between oxygen and hemoglobin was weaker, which was conducive to the release of oxygen to tissue ( Balcerek et al, 2020 ). So far, the existing data showed that there was no significant difference in circulating mir-199a-5p levels between men and women regardless of physiological and disease conditions ( Sanfiorenzo et al, 2013 ; Cammarata et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another point is the Hill coefficient that describes the cooperativity of oxygen binding, meaning the steepness of the slope of the ODC. As a leftward shift is associated with higher steepness of ODC, 11 the effect of elevated Hb‐O 2 affinity is stronger at high sO 2 (lung) compared to lower sO 2 (tissue). Thus, one would expect that in hypoxemia the beneficial effect of improved oxygen uptake would excel the accompanied lowered oxygen release to the tissue.…”
mentioning
confidence: 99%
“…Hydrogen ions, pCO 2 and temperature are crucial determinants of acute adaptation in Hb‐O 2 affinity during elevated workload, but are strictly regulated by other mechanisms and cannot serve for adaptation in the long‐term. 11 , 16 , 17 , 18 The most important modifier of Hb‐O 2 affinity at rest is 2,3‐BPG that binds and stabilizes the T (tense)‐state of Hb. 2,3‐BPG binding to Hb results in a decrease in Hb‐O 2 affinity (rightward shift of ODC) and increase in the delivery of oxygen to the tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation